Transformation and self-identity: Student narratives in post-apartheid South Africa - Frans Kamsteeg (Transformation in Higher Education, 2016)
Organisational change processes are by nature complex and often highly contested. This is particularly true of the transformation South African institutions of higher education have been going through since the end of the apartheid era. Using a narrative approach, this article presents a multi-faceted range of stories by the University of the Free State (UFS) students who took part in a particular leadership programme designed to make a contribution to institutional, and even, societal change. The plurivocality of the identity work the UFS students’ stories display is based on their ethnic, gender and class diversity. It is the context-sensitive ‘tales of the field’ they tell that might help to understand why the transformation concept as well the various transformation-driven practices in higher education are so ambiguous and contested.